A cláusula de perfil no contrato de seguro automóvel e os reflexos no Código de Defesa do Consumidor - Furck, Christiane Hessler (2008)
The technological advance, the scientific progress, the industrial park and the population accumulations have caused the social-economic development, however they have increased the incidence of the patrimonial risks. Insurance contract corresponds to the social-economical development, however it does not translate one legal transaction only as it can mean an infinity of contractual relations, that involve many different people, in innumerable branches of the insurance market. It occurs that the insurance contract can be translated by contract of civil liability insurance, contract of safety from contractual guarantees, contract of residential insurance, contract of health insurance, contract of enterprise insurance, contract of bail insurance, contract of educational insurance, and the contract of vehicule insurance, the target of this study. In this context, the risk should be deeply analyzed, it will have to be declared by the insured, being certain that it is consolidated through the questionnaire of risk evaluation, which should be part of the the insurance proposal. The questionnaire of risk evaluation is also known as a clause of insured profile and its major goal is to personalise and delimit the risk so that the insurer can accept or refuse the insurance proposal and establish the prize of the insurance. This study also analyzes the positive and negative aspects of the clause of profile ahead of the rules established for the Consumer Defense Code